Paradigmen von Animalität - Sabine Wilke (Recherches Germaniques)
Following the publication of the fourth part of his “Alle Toten fliegen hoch” project, Die Zweisamkeit der Einzelgänger, in 2017 actor, director, author, and theater practitioner Joachim Meyerhoff appeared on various talk shows on German TV. With this cycle of autofictional prose planned for six parts, Meyerhoff presents the chronicle of his upbringing in rural Northern Germany as the son of the director of a psychiatric clinic, his year as an exchange student in Wyoming, his years of study at a famous acting school in Munich, and in the just released fourth part his early years as a young actor in the German province. Die Zweisamkeit der Einzelgänger picks as its central topic the relationship between humans and animals and its stage representation. My essay focuses on the analysis of this relationship. In his work for the theater the autofictional narrator examines the parameters for the staging of human-animal relations and reflects critically on their constitution by making visible the inherent power structures that determine that relationship.